Development of Android-Based Interactive Learning Media on Nahwu Subjects in Class XI Madrasah Aliyah Ibnu Taimiyah Bogor - Anthon Budiarjo; Zainal Abidin Arief; Rudi Hartono (Indonesian Journal of Pedagogy and Teacher Education, 2024)
In Nahwu Class XI Madrasah Aliyah Ibnu Taimiyah Bogor in Chapter Khobar Muqoddam Mumtada' Muakhor, the study intends to: 1) ascertain the process for developing Android-based Interactive Learning Media; 2) ascertain the viability of developing Android-based Interactive Learning Media in Nahwu Class XI Madrasah Aliyah Ibnu Taimiyah Bogor in Chapter Khobar Muqoddam Mumtada' Muakhor; and 3) ascertain the efficacy of developing Android-based Interactive Learning Media in Nahwu Class XI Madrasah Aliyah Ibnu Taimiyah Bogor in Chapter Khobar Muqoddam Mumtada' Muakhor. This study employs the research and development methodology (Research and Development). The results of the hypothesis test indicate that there is a significant difference between the pretest and posttest data for nahwu learning outcomes, with a significance value of 0.000 <0.05.